BS EN 16272-2. Railway applications. Infrastructure. Noise barriers and related devices acting on airborne sound propagation. Test method for determining the acoustic performance. Part 2. Intrinsic characteristics. Airborne sound insulation in the laboratory under diffuse sound field conditions (17th February 2022) - British Standards Institution,
No abstract available